The Effect Of Poverty, Unemployment, And Investment On Economic Growth In The Province Of North Sumatera in 2001-2020 - Muammar Rinaldi; Dwi Verasuna Manik; Nova Khairunisa Putri; Joshua Hutagalung; Rico Ramadhanu (Outline Journal of Economic Studies, 2024)
The purpose of this study is to determine the effect of poverty, unemployment and investment on economic growth. Where this study uses time series data with the time period 2001-2020. The analytical method uses multiple linear regression with the Eviews program. The poor population variable has a negative and significant effect on poverty with a t-value of -3.225849 and Prob. of 0.0053 <0.05. Unemployment variable has a negative and insignificant effect on poverty with a t-value of -0.427385 and Prob. 0.6748 > 0.05. The investment variable has a positive and significant effect on poverty with a t-value of 7.932790 and Prob. of 0.0000 <0.05. In the final stage of the statistical test, it is known that the R2 squared value is 0.954978. This shows that the poor, unemployment, and investment are able to explain GRDP by 95%. And the remaining 5% is influenced by other variables not examined in this study.